Factors Affecting the Outcome of Breast Reconstruction Surgery in Modified Radical Mastectomy Procedure - Wahyu Hendra Prabowo; Najatullah (HM Publisher, 2023)
Background: Breast cancer is the leading cause of death in women caused by cancer. The primary treatment for breast cancer is surgery, where several recommended surgical methods are breast-conserving surgery or mastectomy. Postoperative mastectomy reconstruction has provided an opportunity to overcome the emotional and aesthetic burden of malignancy. Methods: This research is a descriptive observational study with a retrospective approach. The sample was 45 breast cancer patients who had undergone a modified radical mastectomy operation at Dr. Kariadi General Hospital for January 2019 - April 2023. The data were processed using SPSS for Windows software, and a descriptive analysis was carried out. Results: Most of the patients who underwent post-MRM breast reconstruction were in the age group >40 years (71.1%), had stage 2 mammary carcinoma (44.4%) and stage 3 (40%), featured invasive ductal carcinoma (84 .4%), breast on the right side (64.4%). Some suffer from hypertension (13.3%) or diabetes mellitus (22.2%). The most used type of reconstruction was STSG (82.2%). A small proportion of patients experienced dehiscence (17.8%). In the Karnofsky score assessment, the highest score was 70 (64.4%), followed by 60 (17.8%), 80 (11.1%), 50 (4.4%), and 40 (2.2%). Conclusion: The patients undergoing MRM are dominated by the age group > 40 years, not suffering from hypertension or diabetes mellitus, stage 2, histopathology of invasive ductal carcinoma, right-sided breast. STSG dominates the choice of reconstruction with postoperative complications in the form of dehiscence in a small proportion of patients. The Karnofsky score is dominated by a score of 70.